Access and Quality in Canada's Parallel Public Healthcare Systems: Is the Impact of Workers' Compensation Boards a Net Positive? - Carolyn Hughes Tuohy (Law & Governance, 2008)
[This article was originally published in HealthcarePapers, Volume 8, Number 3.] Jerry Hurley and his colleagues have done a major service in casting light on a dimension of public healthcare policy in Canada that normally flies under the radar of both public and academic debate. Workers' compensation represents less than 2% of public healthcare expenditures in Canada, and the care provided is concentrated in a few categories such as orthopedics. Nonetheless, the transformation of workers' compensation boards (WCBs) from "silent payers" to increasingly sophisticated and entrepreneurial purchasers of care may have important implications and lessons for the broader healthcare system.